EUS-guided trans-esophageal drainage of a mediastinal necrotic fluid collection using the axios electrocautery enhanced delivery system™. (1st February 2019) - Pizzicannella, Margherita; Pandolfi, Monica; Andrisani, Gianluca; Signoretti, Marianna; Martino, Margareth; Rea, Roberta; Di Matteo, Francesco Maria
Abstract: Mediastinal collection secondary to necrotic acute pancreatitis, is an extremely rare event caused by the posterior rupture of the pancreatic duct into the retroperitoneal space with the penetration of the pancreatic fluid through the diaphragmatic orifices. Infection of the necrotic collection may occur with a consequent substantial increase of the mortality rate. Due to the rarity of this severe condition, no consensus is known about the management of infected mediastinal necrotic collections. We reported the case of a 61-year-old male who was critically unwell secondary to a large mediastinal necrotic collections after necrotic acute pancreatitis with no improvement after surgery. The patient was successfully treated by EUS-guided trans-esophageal drainage using the AXIOS Electrocautery Enhanced Delivery System™. This procedure proved in this case to be a safe and effective option for the management of infected necrotic mediastinal collections.